2015
DOI: 10.1111/cge.12534
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial variability of ZRS‐associated syndrome: characterization of a mosaic ZRS mutation by pyrosequencing

Abstract: During limb development, the spatio-temporal expression of sonic hedgehog (SHH) is driven by the Zone of polarizing activity Regulatory Sequence (ZRS), located 1 megabase upstream from SHH. Gain-of-function mutations of this enhancer, which cause ectopic expression of SHH, are known to be responsible for congenital limb malformations with variable expressivity, ranging from preaxial polydactyly or triphalangeal thumbs to polysyndactyly, which may also be associated with mesomelic deficiency. In this report, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…All ZRS variants tested in this study, including previously published human variants (Al-Qattan et al, 2012;Albuisson et al, 2011;Baas et al, 2017;Cai et al, 2019;Cho et al, 2013;Farooq et al, 2010;Furniss et al, 2008;Girisha et al, 2014;Gurnett et al, 2007;Heutink et al, 1994;Lettice et al, 2003;Lodder, 2009;Norbnop et al, 2014;Semerci et al, 2009;VanderMeer et al, 2012;Vanlerberghe et al, 2015;Wieczorek et al, 2010;Wu et al, 2016;Zguricas et al, 1999;Zhang et al, 2019), variants from animals (Dorshorst et al, 2010;Dunn et al, 2011;Knudsen and Kochhar, 1981;Lettice et al, 2008;Masuya et al, 2007;Zhao et al, 2009) and novel variants reported in this study. Table S1 contains the following columns: variant coordinate in GRCh38 genome assembly (1 st column), relative position within the ZRS enhancer (2 nd column), reference and variant alleles (3 rd column), variant name (4 th column), organism of origin (5 th column), VISTA ID of the tested construct containing the human ZRS enhancer with the variant (6 th column), variant classification based on the enSERT result (7 th column), reference (8-9 th columns), clinical phenotypes and human genetics data for variants from human patients (10-24 th columns), PhyloP scores (25 th column), predicted TF binding sites…”
Section: Table S1 Related To Figure 2 [See Separate Excel File]mentioning
confidence: 98%
“…All ZRS variants tested in this study, including previously published human variants (Al-Qattan et al, 2012;Albuisson et al, 2011;Baas et al, 2017;Cai et al, 2019;Cho et al, 2013;Farooq et al, 2010;Furniss et al, 2008;Girisha et al, 2014;Gurnett et al, 2007;Heutink et al, 1994;Lettice et al, 2003;Lodder, 2009;Norbnop et al, 2014;Semerci et al, 2009;VanderMeer et al, 2012;Vanlerberghe et al, 2015;Wieczorek et al, 2010;Wu et al, 2016;Zguricas et al, 1999;Zhang et al, 2019), variants from animals (Dorshorst et al, 2010;Dunn et al, 2011;Knudsen and Kochhar, 1981;Lettice et al, 2008;Masuya et al, 2007;Zhao et al, 2009) and novel variants reported in this study. Table S1 contains the following columns: variant coordinate in GRCh38 genome assembly (1 st column), relative position within the ZRS enhancer (2 nd column), reference and variant alleles (3 rd column), variant name (4 th column), organism of origin (5 th column), VISTA ID of the tested construct containing the human ZRS enhancer with the variant (6 th column), variant classification based on the enSERT result (7 th column), reference (8-9 th columns), clinical phenotypes and human genetics data for variants from human patients (10-24 th columns), PhyloP scores (25 th column), predicted TF binding sites…”
Section: Table S1 Related To Figure 2 [See Separate Excel File]mentioning
confidence: 98%
“…The ZRS 417 A>G mutation presented with a very unique phenotype of mirror-image polydactyly of the four extremities and bilateral tibial deficiency [ 20 ]. Interestingly, the same mutation in a mosaic form resulted in isolated triphalangeal thumb or thumb duplication with a triphalangeal component (PPD type II) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have emphasized that ZRS point mutations resulting in Werner syndrome (which has PPD-LPAD association in the phenotype) have “strong” ectopic anterior SHH expression [ 16 ]. Further evidence regarding this strong anterior expression comes from appearance of mirror-image duplication of the hands and feet in some patients with ZRS point mutations [ 20 ]. Experimentally, transplantation of few SHH expressing cells to the anterior limb bud results in PPD.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear why the disruption of SHH causes TPT in one family member and a subclinical phenotype in another. One example of how intrafamilial variability can be explained is based on a reported family, where different degrees of somatic mosaicism were associated with various phenotypes in affected family members 22. As the regulatory function of ZRS on SHH is extremely delicate and affected by timing, location and level of activity, it is plausible that the slightest alteration of one of these factors can cause this interindividual phenotypical variation.…”
Section: Discussionmentioning
confidence: 99%